The Association of the Secret, Guilt, and Ego Defence Mechanism in the Novel and Then There Were None - Shafira Aulia (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2020)
And Then There Were None is about ten strangers who are lured to a remote island on August 8th, 1940s. Each of these ten characters harbor deep secret that they have been complicit in the deaths of other person(s) but either escaped justice or deemed innocent. The theme of guilt played in this novel an important role in the novel because it showed how the characters’ minds worked. Fictional character is designed to closely resemble real human beings, and thus their minds can be psychologically analyzed just like real people using Sigmund Freud’s psychoanalytic theories. Using this theory, this study psychoanalyzed four characters from the novel And Then There Were None by Agatha Christie. The objective of this study is to identify the correlation of secret and guilt that affect the characters’ psyche and elicited the use of defense mechanisms. The findings of this study showed that the characters’ conscious act of keeping secret has unconscious repercussions on their psyche. The characters kept secret that they have been complicit in the death of other people, and thus the guilt from that event is repressed into the unconscious mind. The defense mechanism is then employed to keep the upsetting guilt hidden and away from consciousness. The repressed guilt slowly builds up and manifests in various symptoms until it finally resurfaces to the conscious mind.